Liquid crystal composition and liquid crystal display element

The liquid crystal composition with compounds of formula (1) addresses temperature and anisotropy issues, enhancing stability and performance in liquid crystal displays by optimizing viscosity and dielectric properties.

JP2025009974APending Publication Date: 2025-01-20JNC PETROCHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024103056
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-06-25
Filing Date
2024-06-26
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing liquid crystal compositions face challenges with high upper and low lower temperature limits of the nematic phase, high viscosity, inappropriate optical anisotropy, large dielectric constant anisotropy, and frequency-dependent dielectric constant at low temperatures, leading to display defects and reduced performance in liquid crystal display elements.

Method used

A liquid crystal composition containing compounds represented by formula (1) with positive dielectric anisotropy, optimized for specific ratios and additives to enhance properties such as low viscosity, high stability, and balanced dielectric and optical anisotropy, suitable for active matrix elements.

Benefits of technology

The composition achieves improved temperature stability, reduced viscosity, enhanced dielectric and optical anisotropy, and increased voltage holding ratio, resulting in better contrast and longer lifetime of liquid crystal display elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009974000001
    Figure 2025009974000001
  • Figure 2025009974000002
    Figure 2025009974000002
  • Figure 2025009974000003
    Figure 2025009974000003
Patent Text Reader

Abstract

To provide: a liquid crystal composition which satisfies at least one property out of high upper limit temperature, low lower limit temperature, small viscosity, appropriate optical anisotropy, large dielectric anisotropy, large dielectric constant in the short axis direction, large ratio of dielectric constant in the short axis direction to dielectric anisotropy, large specific resistance, high stability to light and heat, large elastic constant and the like, or has suitable balance between at least two properties; and an AM element containing the composition.SOLUTION: A liquid crystal composition contains a specific compound having large optical anisotropy as a component A, and may contain a specific compound having large dielectric anisotropy as a component B, a specific compound having small viscosity or high upper limit temperature as a component C, or a specific compound having large dielectric constant in the short axis direction as a component D.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal composition, a liquid crystal display device containing the composition, etc. In particular, the present invention relates to a liquid crystal composition having positive dielectric anisotropy, and an AM (active matrix) device containing the composition and having a TN, ECB, OCB, IPS, FFS, or FPA mode. [Background technology]

[0002] LCD devices are classified based on the operating mode of the liquid crystal molecules into modes such as PC (phase change), TN (twisted nematic), STN (super twisted nematic), ECB (electrically controlled birefringence), OCB (optically compensated bend), IPS (in-plane switching), VA (vertical alignment), FFS (fringe field switching), and FPA (field-induced photo-reactive alignment). Devices are classified based on their driving method into PM (passive matrix) and AM (active matrix). PM is classified into static, multiplex, etc., and AM is classified into TFT (thin film transistor), MIM (metal insulator metal), etc. TFTs are classified into amorphous silicon and polycrystal silicon. The latter is classified into high temperature type and low temperature type depending on the manufacturing process. Classification based on the light source includes reflective types that use natural light, transmissive types that use backlight, and semi-transmissive types that use both natural light and backlight.

[0003] A liquid crystal display element contains a liquid crystal composition having a nematic phase. This composition has suitable characteristics. By improving the characteristics of this composition, an AM element having good characteristics can be obtained. The relationship between these characteristics is summarized in Table 1 below. The characteristics of the composition will be further explained based on a commercially available AM ​​element. The temperature range of the nematic phase is related to the temperature range in which the element can be used. The preferred upper limit temperature of the nematic phase is about 70°C or higher, and the preferred lower limit temperature of the nematic phase is about -10°C or lower. The viscosity of the composition is related to the response time of the element. A short response time is preferable for displaying moving images with the element. A response time shorter than 1 millisecond is desirable. Therefore, a small viscosity in the composition is preferable. A small viscosity at a low temperature is even more preferable. The elastic constant of the composition is related to the contrast of the element. To increase the contrast in the element, a large elastic constant in the composition is preferable.

[0004] TIFF2025009974000001.tif67152

[0005] The optical anisotropy of the composition is related to the contrast ratio of the element. Depending on the mode of the element, large or small optical anisotropy, i.e., appropriate optical anisotropy, is required. The product (Δn×d) of the optical anisotropy (Δn) of the composition and the cell gap (d) of the element is designed to maximize the contrast ratio. The appropriate value of the product depends on the type of operation mode. For elements in a mode such as TN, the appropriate value is about 0.45 μm. In this case, a composition having large optical anisotropy is preferred for elements with a small cell gap. Large dielectric anisotropy in the composition contributes to a low threshold voltage, small power consumption, and a large contrast ratio in the element. Therefore, a large dielectric anisotropy is preferred. Dielectric anisotropy generally has frequency dependence at low temperatures and becomes smaller as the frequency increases. For this reason, as the driving frequency increases at low temperatures, the movement of the liquid crystal molecules cannot keep up with the frequency change of the voltage, resulting in display defects. Therefore, it is preferable that the frequency dependence of the dielectric anisotropy at low temperatures is small. A large resistivity in a composition contributes to a large voltage holding ratio and a large contrast ratio in an element. Therefore, a composition having a large resistivity in the initial stage is preferable. A composition having a large resistivity after long-term use is preferable. The stability of a composition against ultraviolet light and heat is related to the life of a liquid crystal display element. When these stabilities are high, the life of the element is long. Such characteristics are preferable for AM elements used in liquid crystal monitors, liquid crystal televisions, etc.

[0006] In an AM element having a TN mode, a composition having a positive dielectric anisotropy is used. In an AM element having a VA mode, a composition having a negative dielectric anisotropy is used. In an AM element having a polymer sustained alignment (PSA) type, a composition having a positive or negative dielectric anisotropy is used.

[0007] In order to satisfy the required characteristics of liquid crystal display elements as described above, various compounds have been investigated, and in recent years, compounds having a heterocycle containing sulfur have been developed (Patent Documents 1 and 2, etc.).

[0008] Compounds having a thiadiazole ring as a sulfur-containing heterocycle have been studied for a long time, but most of the studies relate to ferroelectric liquid crystals (Patent Document 3, etc.). As for applications other than ferroelectric liquid crystals, Patent Document 4 discloses a composition containing a compound having a thiadiazole ring as an example of a composition that can be used in a specific device, a vertically aligned sprayed nematic liquid crystal display device.

[0009] Thus, compounds having a thiadiazole ring have only been studied so far for specific applications, and have not been studied for use in general-purpose liquid crystal display devices. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2020-79385 A [Patent Document 2] JP 2021-165367 A [Patent Document 3] Japanese Patent Application Publication No. 10-213820 [Patent Document 4] International Publication No. 1997 / 012275 Summary of the Invention [Problem to be solved by the invention]

[0011] The object of the present invention is to provide a liquid crystal composition that satisfies at least one of the following characteristics: a high maximum temperature of the nematic phase, a low minimum temperature of the nematic phase, a small viscosity, suitable optical anisotropy, a large dielectric anisotropy, a large dielectric constant in the minor axis direction (ε⊥), a large ratio of the dielectric constant in the minor axis direction to the dielectric anisotropy (ε⊥ / Δε), a large resistivity, high stability to light, high stability to heat, and a large elastic constant, and a liquid crystal display element that satisfies at least one of the following characteristics: a short response time, a low threshold voltage, etc. Another object is to provide a liquid crystal composition that has a suitable balance between at least two of the following characteristics: a high maximum temperature of the nematic phase, a low minimum temperature of the nematic phase, a small viscosity, suitable optical anisotropy, a large dielectric anisotropy, a large dielectric constant in the minor axis direction, a large ratio of the dielectric constant in the minor axis direction to the dielectric anisotropy (ε⊥ / Δε), a large resistivity, high stability to light, high stability to heat, and a large elastic constant. Another object is to provide an AM element having characteristics such as a large voltage holding ratio, a large contrast ratio, and a long life. [Means for solving the problem]

[0012] The present invention relates to a liquid crystal composition containing at least one compound selected from the compounds represented by formula (1) as component A and having positive dielectric anisotropy, and a liquid crystal display device containing this composition. TIFF2025009974000002.tif1580 In formula (1), R 1 and R 2is hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkenyl having 2 to 5 carbon atoms, alkenyloxy having 2 to 5 carbon atoms, or alkyl having 1 to 5 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring A and ring B are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-dioxane, 1,4-phenylene, or 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine; X is sulfur or oxygen; a is 1, 2, or 3; b is 0 or 1; and the sum of a and b is 3 or less. Effect of the Invention

[0013] The advantages of the present invention are to provide a liquid crystal composition that satisfies at least one of the following characteristics: a high maximum temperature of the nematic phase, a low minimum temperature of the nematic phase, a small viscosity, suitable optical anisotropy, a large dielectric anisotropy, a large dielectric constant in the minor axis direction (ε⊥), a large ratio of the dielectric constant in the minor axis direction to the dielectric anisotropy (ε⊥ / Δε), a large resistivity, high stability to light, high stability to heat, and a large elastic constant, and a liquid crystal display device that satisfies at least one of the following characteristics: a short response time, a low threshold voltage, etc. Another advantage is to provide a liquid crystal composition that has a suitable balance between at least two of the following characteristics: a high maximum temperature of the nematic phase, a low minimum temperature of the nematic phase, a small viscosity, suitable optical anisotropy, a large dielectric anisotropy, a large dielectric constant in the minor axis direction, a large ratio of the dielectric constant in the minor axis direction to the dielectric anisotropy (ε⊥ / Δε), a large resistivity, high stability to light, high stability to heat, and a large elastic constant. Another advantage is to provide an AM element having characteristics such as a large voltage holding ratio, a large contrast ratio, and a long life. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The terms used in this specification are as follows. The terms "liquid crystal composition" and "liquid crystal display element" may be abbreviated to "composition" and "element", respectively. "Liquid crystal display element" is a general term for liquid crystal display panels and liquid crystal display modules. "Liquid crystal compound" is a general term for compounds having a liquid crystal phase such as a nematic phase or a smectic phase, and compounds that do not have a liquid crystal phase but are mixed into a composition for the purpose of adjusting properties such as the temperature range, viscosity, and dielectric anisotropy of the nematic phase. This compound has a six-membered ring such as 1,4-cyclohexylene or 1,4-phenylene, and its molecules (liquid crystal molecules) are rod-like. "Polymerizable compound" is a compound added to a composition for the purpose of generating a polymer. Liquid crystal compounds having alkenyl are not classified as polymerizable compounds in this sense.

[0015] A liquid crystal composition is prepared by mixing a plurality of liquid crystal compounds. Additives such as optically active compounds and polymerizable compounds are added to this liquid crystal composition as necessary. The proportion of the liquid crystal compound is expressed as a mass percentage (mass%) based on the mass of the liquid crystal composition not including the additive, even when the additive is added. The proportion of the additive is expressed as a mass percentage (mass%) based on the mass of the liquid crystal composition not including the additive. In other words, the proportion of the liquid crystal compound and the additive is calculated based on the total mass of the liquid crystal compound. The proportion of the polymerization initiator and the polymerization inhibitor is exceptionally expressed based on the mass of the polymerizable compound.

[0016] "Upper limit temperature of nematic phase" is sometimes abbreviated as "upper limit temperature". "Lower limit temperature of nematic phase" is sometimes abbreviated as "lower limit temperature". The expression "increase dielectric anisotropy" means that the value increases positively in the case of a composition with positive dielectric anisotropy, and that the value increases negatively in the case of a composition with negative dielectric anisotropy. "Large voltage holding ratio" means that the element has a large voltage holding ratio not only at room temperature but also at temperatures close to the upper limit temperature in the initial stage, and that after long-term use, it has a large voltage holding ratio not only at room temperature but also at temperatures close to the upper limit temperature. The characteristics of a composition or element may be examined by an aging test.

[0017] TIFF2025009974000003.tif2071 The above compound (1z) is taken as an example. In formula (1z), the symbols α and β surrounded by a hexagon correspond to ring α and ring β, respectively, and represent rings such as six-membered rings and fused rings. When the subscript 'x' is 2, there are two rings α. The two groups represented by the two rings α may be the same or different. This rule applies to any two rings α when the subscript 'x' is greater than 2. This rule also applies to other symbols, such as the bond group Z. The diagonal line across one side of ring β represents that any hydrogen on ring β may be replaced with a substituent (-Sp-P). The subscript 'y' indicates the number of replaced substituents. When the subscript 'y' is 0, there is no such replacement. When the subscript 'y' is 2 or more, there are multiple substituents (-Sp-P) on ring β. In this case, the rule that "may be the same or different" also applies. This rule also applies when the symbol Ra is used for multiple compounds.

[0018] In formula (1z), for example, a phrase such as "Ra and Rb are alkyl, alkoxy, or alkenyl" means that Ra and Rb are independently selected from the group of alkyl, alkoxy, and alkenyl, where the group represented by Ra and the group represented by Rb may be the same or different.

[0019] At least one compound selected from the compounds represented by formula (1z) may be abbreviated as "compound (1z)". "Compound (1z)" means one compound represented by formula (1z), a mixture of two compounds, or a mixture of three or more compounds. The same applies to compounds represented by other formulas. The expression "at least one compound selected from the compounds represented by formula (1z) and formula (2z)" means at least one compound selected from the group of compounds (1z) and compounds (2z).

[0020] The expression "at least one 'A'" means that the number of 'A' is arbitrary. The expression "at least one 'A' may be replaced with 'B'" means that when the number of 'A' is one, the position of 'A' is arbitrary, and when the number of 'A' is two or more, the positions can be selected without restriction. The expression "at least one -CH2- may be replaced with -O-" is sometimes used. In this case, -CH2-CH2-CH2- may be converted to -O-CH2-O- by replacing non-adjacent -CH2- with -O-. However, adjacent -CH2- cannot be replaced with -O- because this replacement generates -OO-CH2- (peroxide).

[0021] The alkyl of the liquid crystal compound is linear or branched, and does not include cyclic alkyl. Linear alkyl is more preferable than branched alkyl. The same applies to terminal groups such as alkoxy and alkenyl. The stereoconfiguration of 1,4-cyclohexylene is preferably trans rather than cis in order to increase the upper limit temperature. 2-Fluoro-1,4-phenylene is asymmetric, so it exists in left-facing (L) and right-facing (R) configurations. TIFF2025009974000004.tif25111 The same is true for divalent groups such as tetrahydropyran-2,5-diyl, and for linking groups such as carbonyloxy (-COO- or -OCO-).

[0022] The present invention includes the following items.

[0023] Item 1. A liquid crystal composition having positive dielectric anisotropy, comprising as component A at least one compound selected from the compounds represented by formula (1): TIFF2025009974000005.tif1580 In formula (1), R 1 and R 2is hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkenyl having 2 to 5 carbon atoms, alkenyloxy having 2 to 5 carbon atoms, or alkyl having 1 to 5 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring A and ring B are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-dioxane, 1,4-phenylene, or 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine; X is sulfur or oxygen; a is 1, 2, or 3; b is 0 or 1; and the sum of a and b is 3 or less.

[0024] Item 2. The liquid crystal composition according to item 1, comprising, as component A, at least one compound selected from the compounds represented by formulae (1-1) to (1-8): TIFF2025009974000006.tif16197 In formulas (1-1) to (1-8), R 1 and R 2 is hydrogen, alkyl having 1 to 5 carbons, alkoxy having 1 to 5 carbons, alkenyl having 2 to 5 carbons, alkenyloxy having 2 to 5 carbons, or alkyl having 1 to 5 carbons in which at least one hydrogen is replaced by fluorine or chlorine; and Y is hydrogen, fluorine, or chlorine.

[0025] Item 3. The liquid crystal composition according to item 1 or 2, wherein the proportion of component A is in the range of 3% by mass to 30% by mass.

[0026] Item 4. The liquid crystal composition according to any one of items 1 to 3, comprising, as component B, at least one compound selected from the compounds represented by formula (2) and formula (3): TIFF2025009974000007.tif51104 In formula (2), R 3is alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, or alkenyl having 2 to 12 carbon atoms; ring C is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, 2,3-difluoro-1,4-phenylene, 2,6-difluoro-1,4-phenylene, pyrimidine-2,5-diyl, 1,3-dioxane-2,5-diyl, or tetrahydropyran-2,5-diyl; Z 1 is a single bond, ethylene, vinylene, carbonyloxy, or difluoromethyleneoxy; X 1 and X 2 is hydrogen or fluorine; Y 1 is fluorine, chlorine, alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, alkoxy having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, or alkenyloxy having 2 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine; c is 1, 2, 3, or 4; In formula (3), R 4 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms; ring D is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,6-difluoro-1,4-phenylene; Z 2 is a single bond, carbonyloxy, or difluoromethyleneoxy; X 3 and X 4 is hydrogen or fluorine; and d is 1, 2, 3, or 4.

[0027] Item 5. The liquid crystal composition according to any one of items 1 to 4, comprising, as component B, at least one compound selected from the compounds represented by formulas (2-1) to (2-36) and formulas (3-1) to (3-8). TIFF2025009974000008.tif212124 TIFF2025009974000009.tif212126 TIFF2025009974000010.tif218125 TIFF2025009974000011.tif245126 TIFF2025009974000012.tif218112 In formulas (2-1) to (2-36), R 3 is alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, or alkenyl having 2 to 12 carbons; In formulas (3-1) to (3-8), R 4 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms; X 3 and X 4 is hydrogen or fluorine.

[0028] Item 6. The liquid crystal composition according to item 4 or 5, wherein the proportion of component B is in the range of 5% by mass to 50% by mass.

[0029] Item 7. The liquid crystal composition according to any one of items 1 to 6, comprising, as component C, at least one compound selected from the compounds represented by formula (4): TIFF2025009974000013.tif1580 In formula (4), R 5 and R 6 is an alkyl having 1 to 12 carbon atoms, an alkoxy having 1 to 12 carbon atoms, an alkenyl having 2 to 12 carbon atoms, or an alkenyl having 2 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring E and ring F are 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,5-difluoro-1,4-phenylene; Z 3 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy; and e is 1, 2, or 3.

[0030] Item 8. The liquid crystal composition according to any one of items 1 to 7, comprising, as component C, at least one compound selected from the compounds represented by formulae (4-1) to (4-15): TIFF2025009974000014.tif175107 TIFF2025009974000015.tif88108 In formulas (4-1) to (4-15), R 5 and R 6 is alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, alkenyl having 2 to 12 carbons, alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, or alkenyl having 2 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine.

[0031] Item 9. The liquid crystal composition according to item 7 or 8, wherein the proportion of component C is in the range of 10% by mass to 85% by mass.

[0032] Item 10. The liquid crystal composition according to any one of items 1 to 9, comprising at least one compound selected from the compounds represented by formula (5) as component D: TIFF2025009974000016.tif17110 In formula (5), R 7 and R 8is hydrogen, alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, alkenyl having 2 to 12 carbon atoms, alkenyloxy having 2 to 12 carbon atoms, or alkyl having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring G and ring J are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-phenylene, 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine, naphthalene-2,6-diyl, naphthalene-2,6-diyl in which at least one hydrogen is replaced by fluorine or chlorine, chroman-2,6-diyl, or at least one water group. ring I is 2,3-difluoro-1,4-phenylene, 2-chloro-3-fluoro-1,4-phenylene, 2,3-difluoro-5-methyl-1,4-phenylene, 1,8-difluorophenanthrene-2,7-diyl, 3,4,5-trifluoronaphthalene-2,6-diyl, 7,8-difluorochroman-2,6-diyl, 3,4,5,6-tetrafluorofluorene-2,7-diyl, 4,6-difluorodibenzofuran-3,7-diyl, 4,6-difluorodibenzothiophene-3,7-diyl, or 1,1,6,7-tetrafluoroindan-2,5-diyl; 4 and Z 5 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy; f is 0, 1, 2, or 3, g is 0 or 1; and the sum of f and g is 3 or less.

[0033] Item 11. The liquid crystal composition according to any one of items 1 to 10, comprising, as component D, at least one compound selected from the compounds represented by formulae (5-1) to (5-36): TIFF2025009974000017.tif223110 TIFF2025009974000018.tif221113 TIFF2025009974000019.tif231113 TIFF2025009974000020.tif132115 In formulas (5-1) to (5-36), R 7 and R 8 is hydrogen, alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, alkenyl having 2 to 12 carbons, alkenyloxy having 2 to 12 carbons, or alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine.

[0034] Item 12. The liquid crystal composition according to item 10 or 11, wherein the proportion of component D is in the range of 1% by mass to 20% by mass.

[0035] Item 13. A liquid crystal display device comprising the liquid crystal composition according to any one of items 1 to 12.

[0036] Item 14. The liquid crystal display element according to item 13, wherein the operation mode is TN mode, ECB mode, OCB mode, IPS mode, FFS mode, or FPA mode, and the driving method is an active matrix method.

[0037] Item 15. Use of the liquid crystal composition according to any one of items 1 to 12 in a liquid crystal display device.

[0038] The present invention also includes the following: (a) the above composition containing one compound, two compounds, or three or more compounds selected from additives such as optically active compounds, antioxidants, ultraviolet absorbers, quenchers, dyes, defoamers, polymerizable compounds, polymerization initiators, polymerization inhibitors, and polar compounds; (b) an AM element containing the above composition; (c) the above composition further containing a polymerizable compound, and a polymer supported alignment (PSA) type AM element containing the composition; (d) a polymer supported alignment (PSA) type AM element containing the above composition, in which the polymerizable compound in the composition is polymerized; (e) an element containing the above composition and having a PC, TN, STN, ECB, OCB, IPS, VA, FFS, or FPA mode; (f) a transmission type element containing the above composition; (g) use of the above composition as a composition having a nematic phase; (h) use of an optically active composition obtained by adding an optically active compound to the above composition.

[0039] The composition of the present invention will be described in the following order. First, the constitution of the composition will be described. Second, the main properties of the component compounds and the main effects that these compounds have on the composition and the device will be described. Third, the combination of the component compounds in the composition, the preferred ratios, and the reasons therefor will be described. Fourth, the preferred forms of the component compounds will be described. Fifth, preferred component compounds will be shown. Sixth, additives that may be added to the composition will be described. Seventh, a method for synthesizing the component compounds will be described. Finally, the uses of the composition will be described.

[0040] First, the composition will be described. This composition contains a plurality of liquid crystal compounds. This composition may contain additives. The additives are optically active compounds, antioxidants, ultraviolet absorbers, quenchers, dyes, defoamers, polymerizable compounds, polymerization initiators, polymerization inhibitors, polar compounds, and the like. This composition is classified into composition A and composition B from the viewpoint of liquid crystal compounds. Composition A may further contain other liquid crystal compounds, additives, and the like in addition to the liquid crystal compounds selected from compound (1), compound (2), compound (3), compound (4), and compound (5). "Other liquid crystal compounds" are liquid crystal compounds different from compound (1), compound (2), compound (3), compound (4), and compound (5). Such compounds are mixed into the composition for the purpose of further adjusting the properties.

[0041] Composition B consists essentially of liquid crystal compounds selected from compound (1), compound (2), compound (3), compound (4), and compound (5). "Substantially" means that composition B may contain additives, but does not contain other liquid crystal compounds. Composition B has fewer components than composition A. From the viewpoint of reducing costs, composition B is more preferable than composition A. From the viewpoint of being able to further adjust the properties by mixing other liquid crystal compounds, composition A is more preferable than composition B.

[0042] Secondly, the main properties of the component compounds and the main effects that these compounds have on the composition and device are explained. The main properties of the component compounds are summarized in Table 2. In the symbols in Table 2, L means large or high, M means medium, and S means small or low. The symbols L, M, and S are classifications based on qualitative comparisons between the component compounds, and the symbol 0 (zero) means smaller than S.

[0043] TIFF2025009974000021.tif68163

[0044] The main effects of the component compounds are as follows: Compound (1) decreases the viscosity, increases the optical anisotropy, and increases the dielectric constant in the minor axis direction; Compound (2) and Compound (3) increase the dielectric anisotropy; Compound (4) decreases the viscosity or increases the maximum temperature; and Compound (5) increases the dielectric constant in the minor axis direction.

[0045] Thirdly, the combination of the component compounds in the composition, the preferred ratio, and the basis thereof will be explained. The preferred combination of the component compounds in the composition is compound (1) + compound (2) + compound (4), compound (1) + compound (2) + compound (5), compound (1) + compound (3) + compound (4), compound (1) + compound (3) + compound (5), compound (1) + compound (2) + compound (3) + compound (4), compound (1) + compound (2) + compound (3) + compound (5), compound (1) + compound (2) + compound (4) + compound (5), or compound (1) + compound (2) + compound (3) + compound (4) + compound (5). Particularly preferred combinations are compound (1) + compound (2) + compound (4), compound (1) + compound (2) + compound (3) + compound (4), or compound (1) + compound (2) + compound (4) + compound (5).

[0046] A preferred ratio of compound (1) is about 3% by mass or more for increasing the optical anisotropy and the dielectric constant in the minor axis direction, and about 30% by mass or less for decreasing the minimum temperature. A more preferred ratio is in the range of about 3% by mass to about 20% by mass. A particularly preferred ratio is in the range of about 3% by mass to about 15% by mass.

[0047] A preferred ratio of component B is about 5% by mass or more for increasing the dielectric anisotropy, and about 50% by mass or less for decreasing the minimum temperature. A more preferred ratio is in the range of about 10% by mass to about 40% by mass. A particularly preferred ratio is in the range of about 10% by mass to about 30% by mass.

[0048] A preferred ratio of compound (4) is about 10% by mass or more for decreasing the viscosity or increasing the maximum temperature, and about 85% by mass or less for increasing the dielectric anisotropy. A more preferred ratio is in the range of about 20% by mass to about 85% by mass. A particularly preferred ratio is in the range of about 40% by mass to about 80% by mass.

[0049] A preferred ratio of compound (5) is about 1% by mass or more for increasing the dielectric constant in the minor axis direction, and about 20% by mass or less for decreasing the minimum temperature. A more preferred ratio is in the range of about 5% by mass to about 20% by mass. A particularly preferred ratio is in the range of about 5% by mass to about 15% by mass.

[0050] Fourthly, preferred forms of the component compounds will be described. In the formulas (1), (2), (3), (4), and (5), R 1 and R 2 is hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkenyl having 2 to 5 carbon atoms, alkenyloxy having 2 to 5 carbon atoms, or alkyl having 1 to 5 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine. 1 or R 2 is an alkyl group having 1 to 5 carbon atoms to increase stability. 3 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms. 3 is an alkyl group having 1 to 12 carbon atoms to increase stability. 4 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms. 4 is an alkyl having 1 to 12 carbon atoms to increase stability, and an alkenyl having 2 to 12 carbon atoms to decrease viscosity. 5 and R 6 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms in which at least one hydrogen is replaced by a fluorine or chlorine. 5 or R6 is an alkyl having 1 to 12 carbon atoms to increase stability, and an alkenyl having 2 to 12 carbon atoms to decrease viscosity. 7 and R 8 is hydrogen, alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, alkenyl having 2 to 12 carbon atoms, alkenyloxy having 2 to 12 carbon atoms, or alkyl having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine. 7 or R 8 is an alkyl having 1 to 12 carbon atoms to increase stability, an alkenyl having 2 to 12 carbon atoms to decrease viscosity, and an alkoxy having 1 to 12 carbon atoms to increase the dielectric constant in the minor axis direction.

[0051] Preferred alkyl groups are methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, and octyl. More preferred alkyl groups are methyl, ethyl, propyl, butyl, and pentyl for decreasing the viscosity.

[0052] Preferred alkoxy is methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, or heptyloxy. In order to decrease the viscosity, more preferred alkoxy is methoxy or ethoxy.

[0053] Preferred alkenyls are vinyl, 1-propenyl, 2-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, or 5-hexenyl. More preferred alkenyls are vinyl, 1-propenyl, 3-butenyl, or 3-pentenyl to reduce viscosity. The preferred configuration of -CH=CH- in these alkenyls depends on the position of the double bond. In order to reduce viscosity, trans is preferred in alkenyls such as 1-propenyl, 1-butenyl, 1-pentenyl, 1-hexenyl, 3-pentenyl, and 3-hexenyl. Cis is preferred in alkenyls such as 2-butenyl, 2-pentenyl, and 2-hexenyl.

[0054] Preferred alkenyloxy is vinyloxy, allyloxy, 3-butenyloxy, 3-pentenyloxy, or 4-pentenyloxy. In order to decrease the viscosity, more preferred alkenyloxy is allyloxy or 3-butenyloxy.

[0055] Preferred examples of alkyl in which at least one hydrogen is replaced by fluorine or chlorine include fluoromethyl, 2-fluoroethyl, 3-fluoropropyl, 4-fluorobutyl, 5-fluoropentyl, 6-fluorohexyl, 7-fluoroheptyl, and 8-fluorooctyl. More preferred examples are 2-fluoroethyl, 3-fluoropropyl, 4-fluorobutyl, and 5-fluoropentyl to increase the dielectric anisotropy.

[0056] Preferred examples of alkenyl in which at least one hydrogen is replaced by fluorine or chlorine include 2,2-difluorovinyl, 3,3-difluoro-2-propenyl, 4,4-difluoro-3-butenyl, 5,5-difluoro-4-pentenyl, or 6,6-difluoro-5-hexenyl. More preferred examples are 2,2-difluorovinyl or 4,4-difluoro-3-butenyl to reduce viscosity.

[0057] Ring A and ring B are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-dioxane, 1,4-phenylene, and 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine. Preferred ring A or ring B is 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine to decrease the viscosity or increase the optical anisotropy, and 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine to increase the dielectric constant in the minor axis direction.

[0058] Ring C is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, 2,3-difluoro-1,4-phenylene, 2,6-difluoro-1,4-phenylene, pyrimidine-2,5-diyl, 1,3-dioxane-2,5-diyl, or tetrahydropyran-2,5-diyl. Preferred ring C is 1,4-cyclohexylene for increasing the maximum temperature, 1,4-phenylene for increasing the optical anisotropy, and 2,6-difluoro-1,4-phenylene for increasing the dielectric anisotropy. Tetrahydropyran-2,5-diyl is, TIFF2025009974000022.tif1122 or TIFF2025009974000023.tif1122 and preferably TIFF2025009974000024.tif1122 It is.

[0059] Ring D is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,6-difluoro-1,4-phenylene. Preferred ring D is 1,4-cyclohexylene for increasing the maximum temperature, 1,4-phenylene for increasing the optical anisotropy, and 2-fluoro-1,4-phenylene or 2,6-difluoro-1,4-phenylene for increasing the dielectric anisotropy.

[0060] Ring E and ring F are 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,5-difluoro-1,4-phenylene. Preferred ring E or ring F is 1,4-cyclohexylene for decreasing the viscosity or increasing the maximum temperature, and 1,4-phenylene or 2-fluoro-1,4-phenylene for increasing the optical anisotropy or decreasing the minimum temperature.

[0061] Ring G and ring J are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-phenylene, 1,4-phenylene with at least one hydrogen replaced by fluorine or chlorine, naphthalene-2,6-diyl, naphthalene-2,6-diyl with at least one hydrogen replaced by fluorine or chlorine, chroman-2,6-diyl, or chroman-2,6-diyl with at least one hydrogen replaced by fluorine or chlorine. Preferred examples of "1,4-phenylene with at least one hydrogen replaced by fluorine or chlorine" include 2-fluoro-1,4-phenylene, 2,3-difluoro-1,4-phenylene, or 2-chloro-3-fluoro-1,4-phenylene. Preferred ring G or ring J is 1,4-cyclohexylene for decreasing the viscosity, tetrahydropyran-2,5-diyl for increasing the dielectric constant in the minor axis direction, or 1,4-phenylene for increasing the optical anisotropy. Tetrahydropyran-2,5-diyl in ring G or ring J is TIFF2025009974000025.tif1324 or TIFF2025009974000026.tif1322 and preferably TIFF2025009974000027.tif1322 It is.

[0062] Ring I is 2,3-difluoro-1,4-phenylene, 2-chloro-3-fluoro-1,4-phenylene, 2,3-difluoro-5-methyl-1,4-phenylene, 1,8-difluorophenanthrene-2,7-diyl, 3,4,5-trifluoronaphthalene-2,6-diyl, 7,8-difluorochroman-2,6-diyl, 3,4,5,6-tetrafluorofluorene-2,7-diyl (FLF4), 4,6-difluorodibenzofuran-3,7-diyl (DBFF2), 4,6-difluorodibenzothiophene-3,7-diyl (DBTF2), or 1,1,6,7-tetrafluoroindan-2,5-diyl (InF4). TIFF2025009974000028.tif28166 A preferred ring I is 2,3-difluoro-1,4-phenylene for decreasing the viscosity, and 4,6-difluorodibenzothiophene-3,7-diyl for increasing the dielectric constant in the minor axis direction.

[0063] Z 1 is a single bond, ethylene, vinylene, carbonyloxy, or difluoromethyleneoxy. 1 is a single bond to decrease the viscosity, and is difluoromethyleneoxy to increase the dielectric anisotropy. 2 is a single bond, carbonyloxy, or difluoromethyleneoxy. 2 is a single bond to decrease the viscosity, and is carbonyloxy or difluoromethyleneoxy to increase the dielectric anisotropy. 3 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy. 3 is a single bond to reduce viscosity. Z 4 and Z 5 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy. 4 or Z 5 is a single bond to decrease the viscosity, is ethylene to decrease the minimum temperature, and is methyleneoxy to increase the dielectric constant in the minor axis direction.

[0064] Divalent groups such as methyleneoxy are asymmetric. In methyleneoxy, -CH2O- is preferred over -OCH2-. In carbonyloxy, -COO- is preferred over -OCO-. In difluoromethyleneoxy, -CF2O- is preferred over -OCF2-.

[0065] X is sulfur or oxygen. Desirable X is sulfur for increasing the maximum temperature and the optical anisotropy.

[0066] Y is hydrogen, fluorine or chlorine. Preferred Y is hydrogen for decreasing the viscosity, and fluorine for increasing the dielectric constant in the minor axis direction.

[0067] X 1 and X 2 is hydrogen or fluorine. 1 or X 2 is fluorine to increase the dielectric anisotropy.

[0068] X 3 and X 4 is hydrogen or fluorine. 3 or X 4 is hydrogen for decreasing the viscosity or for increasing the optical anisotropy, or is fluorine for increasing the dielectric anisotropy.

[0069] Y 1 is fluorine, chlorine, alkyl having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine, alkoxy having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine, or alkenyloxy having 2 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine. 1is fluorine, alkyl having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine, or alkoxy having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine in order to increase the dielectric anisotropy. A preferred example of the alkyl in which at least one hydrogen is replaced by fluorine or chlorine is trifluoromethyl. A preferred example of the alkoxy in which at least one hydrogen is replaced by fluorine or chlorine is trifluoromethoxy.

[0070] a is 1, 2, or 3, b is 0 or 1, and the sum of a and b is 3 or less. Preferred a or b is 1 for increasing the optical anisotropy and decreasing the viscosity. c is 1, 2, 3, or 4. Preferred c is 2 for decreasing the viscosity, and 3 for increasing the maximum temperature or increasing the dielectric anisotropy. d is 1, 2, 3, or 4. Preferred d is 1 or 2 for decreasing the minimum temperature. e is 1, 2, or 3. Preferred e is 1 for decreasing the viscosity, and 2 or 3 for increasing the maximum temperature. f is 0, 1, 2, or 3, g is 0 or 1, and the sum of f and g is 3 or less. Preferred f is 0 or 1 for decreasing the viscosity, and 2 for increasing the maximum temperature. Preferred g is 0 for decreasing the viscosity, and 1 for increasing the maximum temperature.

[0071] Fifth, preferred component compounds are shown below. Preferred compound (1) is compound (1-1) to compound (1-8) described in item 2. In these compounds, at least one of component A is preferably compound (1-2).

[0072] Preferred compounds (2) are compounds (2-1) to (2-36) described in item 5. In these compounds, it is preferred that at least one of the components B is a compound (2-2), a compound (2-5), a compound (2-8), a compound (2-13), a compound (2-15), a compound (2-16), a compound (2-17), a compound (2-19), a compound (2-23), a compound (2-24), a compound (2-25), a compound (2-27), a compound (2-28), a compound (2-30), or a compound (2-31). It is more preferred that at least one of the components B is a compound (2-5), a compound (2-15), a compound (2-17), a compound (2-19), a compound (2-23), a compound (2-24), a compound (2-28), a compound (2-30), or a compound (2-31).

[0073] Preferred compounds (3) are compounds (3-1) to (3-8) described in item 5. In these compounds, it is preferred that at least one of the components B is compound (3-1), compound (3-2), compound (3-3), compound (3-7), or compound (3-8). It is more preferred that at least one of the components B is compound (3-1), compound (3-2), or compound (3-7).

[0074] Preferred compounds (4) are compounds (4-1) to (4-15) described in item 8. In these compounds, it is preferred that at least one of the components C is compound (4-1), compound (4-3), compound (4-7), compound (4-8), compound (4-10), or compound (4-12). It is more preferred that at least one of the components C is compound (4-1), compound (4-7), or compound (4-10).

[0075] Preferred compounds (5) are compounds (5-1) to (5-36) described in item 11. In these compounds, it is preferred that at least one of the components D is compound (5-1), compound (5-2), compound (5-3), compound (5-6), compound (5-8), compound (5-9), compound (5-10), compound (5-14), compound (5-19), or compound (5-36). It is more preferred that at least one of the components D is compound (5-8) or compound (5-14).

[0076] Sixth, additives that may be added to the composition will be described. Such additives include optically active compounds, antioxidants, ultraviolet absorbers, quenchers, dyes, defoamers, polymerizable compounds, polymerization initiators, polymerization inhibitors, polar compounds, etc. The optically active compounds are added to the composition for the purpose of inducing a helical structure of the liquid crystal molecules to give a twist angle. Examples of such compounds are compounds (6-1) to (6-5). The preferred ratio of the optically active compounds is about 5% by mass or less. More preferred ratios are in the range of about 0.01% by mass to about 2% by mass.

[0077] TIFF2025009974000029.tif170153

[0078] In order to prevent a decrease in resistivity due to heating in the atmosphere, or in order to maintain a large voltage holding ratio not only at room temperature but also at temperatures close to the upper limit temperature after long-term use of the element, an antioxidant such as compound (7-1) to compound (7-3) may be further added to the composition.

[0079] TIFF2025009974000030.tif87125

[0080] Compound (7-2) has low volatility, so it is effective in maintaining a large voltage holding ratio not only at room temperature but also at temperatures close to the upper limit temperature after the element has been used for a long time. The preferred ratio of the antioxidant is about 50 ppm or more to obtain the effect, and about 600 ppm or less to avoid lowering the upper limit temperature or raising the lower limit temperature. A more preferred ratio is in the range of about 100 ppm to about 300 ppm.

[0081] Preferred examples of the ultraviolet absorber include benzophenone derivatives, benzoate derivatives, triazole derivatives, etc. Light stabilizers such as sterically hindered amines are also preferred. Preferred examples of the light stabilizer include compounds (8-1) to (8-16), etc. The preferred ratio of these absorbers and stabilizers is about 50 ppm or more to obtain the effect, and about 10,000 ppm or less to avoid lowering the maximum temperature or raising the minimum temperature. A more preferred ratio is in the range of about 100 ppm to about 10,000 ppm.

[0082] TIFF2025009974000031.tif250138

[0083] TIFF2025009974000032.tif246138

[0084] A quencher is a compound that receives light energy absorbed by a liquid crystal compound and converts it into thermal energy, thereby preventing the decomposition of the liquid crystal compound. Preferred examples of the quencher include compounds (9-1) to (9-7). The preferred ratio of these quenchers is about 50 ppm or more to obtain the effect, and about 20,000 ppm or less to avoid increasing the minimum temperature. A more preferred ratio is in the range of about 100 ppm to about 10,000 ppm.

[0085] TIFF2025009974000033.tif15979

[0086] In order to adapt the composition to a GH (guest host) mode element, a dichroic dye such as an azo dye or an anthraquinone dye is added to the composition. The preferred ratio of the dye is in the range of about 0.01% by mass to about 10% by mass. In order to prevent foaming, an antifoaming agent such as dimethyl silicone oil or methylphenyl silicone oil is added to the composition. The preferred ratio of the antifoaming agent is about 1 ppm or more to obtain the effect, and about 1000 ppm or less to prevent display defects. The more preferred ratio is in the range of about 1 ppm to about 500 ppm.

[0087] A polymerizable compound is used to adapt the polymerizable compound to a polymer supported alignment (PSA) type element. Preferred examples of such polymerizable compounds are compounds such as acrylate, methacrylate, vinyl compounds, vinyloxy compounds, propenyl ether, epoxy compounds (oxirane, oxetane), and vinyl ketone. More preferred examples are acrylate or methacrylate derivatives. A preferred ratio is about 10% by mass or more based on the total mass of the polymerizable compound. A more preferred ratio is about 50% by mass or more. A particularly preferred ratio is about 80% by mass or more. The most preferred ratio is 100% by mass.

[0088] When storing a polymerizable compound, a polymerization inhibitor may be added to prevent polymerization. The polymerizable compound is usually added to the composition without removing the polymerization inhibitor. Examples of the polymerization inhibitor include hydroquinone, hydroquinone derivatives such as methylhydroquinone, 4-t-butylcatechol, 4-methoxyphenol, phenothiazine, etc.

[0089] A polar compound is an organic compound that has polarity. This does not include compounds with ionic bonds. Atoms such as oxygen, sulfur, and nitrogen tend to be more electronegative and carry a partial negative charge. Carbon and hydrogen tend to be neutral or carry a partial positive charge. Polarity results from the partial charges not being distributed evenly among different atoms in a compound. For example, a polar compound has at least one of the following substructures: -OH, -COOH, -SH, -NH2, >NH, >N-.

[0090] Seventh, the synthesis method of the component compounds will be described. These compounds can be synthesized by known methods. Examples of synthesis methods will be described. A synthesis example of compound (1) is described in the Examples section. Compound (2-19) is synthesized by the method described in JP-A-10-251186. Compound (3-7) is synthesized by the method described in JP-A-10-114733. Compound (4-1) is synthesized by the method described in JP-A-9-77692. Compound (5-1) is synthesized by the method described in JP-T-2-503441. Antioxidants are commercially available. Compound (7-1) is available from Sigma-Aldrich Corporation. Compound (7-2) and the like are synthesized by the method described in U.S. Pat. No. 3,660,505.

[0091] Compounds for which no synthesis method is described can be synthesized by methods described in textbooks such as Organic Syntheses (John Wiley & Sons, Inc.), Organic Reactions (John Wiley & Sons, Inc.), Comprehensive Organic Synthesis (Pergamon Press), and New Experimental Chemistry Lectures (Maruzen). Compositions are prepared from the compounds thus obtained by known methods. For example, the component compounds are mixed and dissolved in each other by heating.

[0092] Finally, the use of the composition is described. This composition mainly has a lower limit temperature of about -10°C or less, an upper limit temperature of about 70°C or more, and an optical anisotropy in the range of about 0.07 to about 0.20. By controlling the ratio of the component compounds or by mixing other liquid crystal compounds, a composition having an optical anisotropy in the range of about 0.08 to about 0.25 may be prepared. By trial and error, a composition having an optical anisotropy in the range of about 0.10 to about 0.30 may be prepared. An element containing this composition has a large voltage holding ratio. This composition is suitable for an AM element. This composition is particularly suitable for a transmission type AM element. This composition can be used as a composition having a nematic phase, or as an optically active composition by adding an optically active compound.

[0093] This composition can be used in AM elements. It can also be used in PM elements. This composition can be used in AM elements and PM elements having modes such as PC, TN, STN, ECB, OCB, IPS, FFS, VA, and FPA. It is particularly preferable to use this composition in AM elements having TN, OCB, IPS, or FFS modes. In AM elements having IPS or FFS modes, when no voltage is applied, the alignment of the liquid crystal molecules may be parallel or perpendicular to the glass substrate. These elements may be reflective, transmissive, or semi-transmissive. It is preferable to use this composition in transmissive elements. It can also be used in amorphous silicon-TFT elements or polycrystalline silicon-TFT elements. It can also be used in NCAP (nematic curvilinear aligned phase) type elements prepared by microencapsulating this composition, and PD (polymer dispersed) type elements in which a three-dimensional network polymer is formed in the composition. EXAMPLES

[0094] The present invention will be described in more detail with reference to examples. The present invention is not limited by these examples. The present invention includes a mixture of the composition of Example 1 and the composition of Example 2. The present invention also includes a mixture of at least two of the compositions of the examples. The synthesized compounds were identified by methods such as NMR analysis. The properties of the compounds, compositions, and elements were measured by the methods described below.

[0095] NMR analysis: For the measurement, a DRX-500 manufactured by Bruker Biospin was used. 1 In the H-NMR measurement, the sample was dissolved in a deuterated solvent such as CDCl3, and the measurement was performed at room temperature, at 500 MHz, and with 16 accumulations. Tetramethylsilane was used as the internal standard. 19 In the F-NMR measurement, CFCl3 was used as an internal standard, and the number of accumulations was 24. In the explanation of the nuclear magnetic resonance spectrum, s means singlet, d means doublet, t means triplet, q means quartet, quin means quintet, sex means sextet, m means multiplet, and br means broad.

[0096] Gas chromatographic analysis: A Shimadzu GC-14B gas chromatograph was used for the measurements. The carrier gas was helium (2 mL / min). The sample vaporizer was set to 280°C, and the detector (FID) to 300°C. Agilent Technologies Inc. capillary column DB-1 (length 30 m, inner diameter 0.32 mm, film thickness 0.25 μm; stationary liquid phase dimethylpolysiloxane; non-polar) was used to separate the component compounds. This column was held at 200°C for 2 minutes, and then heated to 280°C at a rate of 5°C / min. The sample was prepared in acetone (0.1% by mass), and 1 μL of the solution was injected into the sample vaporizer. The recorder was a Shimadzu C-R5A Chromatopac, or equivalent. The obtained gas chromatogram showed the retention times and areas of the peaks corresponding to the component compounds.

[0097] The solvent for diluting the sample may be chloroform, hexane, or the like. The following capillary columns may be used to separate the component compounds: HP-1 (length 30 m, inner diameter 0.32 mm, film thickness 0.25 μm) manufactured by Agilent Technologies Inc., Rtx-1 (length 30 m, inner diameter 0.32 mm, film thickness 0.25 μm) manufactured by Restek Corporation, BP-1 (length 30 m, inner diameter 0.32 mm, film thickness 0.25 μm) manufactured by SGE International Pty. Ltd. In order to prevent overlapping of compound peaks, the capillary column CBP1-M50-025 (length 50 m, inner diameter 0.25 mm, film thickness 0.25 μm) manufactured by Shimadzu Corporation may be used.

[0098] The ratio of the liquid crystal compound contained in the composition may be calculated by the following method. A mixture of liquid crystal compounds is analyzed by gas chromatography (FID). The peak area ratio in the gas chromatogram corresponds to the ratio of the liquid crystal compound. When the capillary column described above is used, the correction coefficient of each liquid crystal compound may be regarded as 1. Therefore, the ratio (mass %) of the liquid crystal compound can be calculated from the peak area ratio.

[0099] Measurement sample: When measuring the properties of a composition or element, the composition was used as it was as a sample. When measuring the properties of a compound, a sample for measurement was prepared by mixing this compound (15% by mass) with mother liquid crystal (85% by mass). The property value of the compound was calculated by extrapolation from the value obtained by measurement. (Extrapolated value) = {(Measured value of sample) - 0.85 x (Measured value of mother liquid crystal)} / 0.15. When a smectic phase (or crystal) precipitates at 25 ° C. at this ratio, the ratio of the compound to the mother liquid crystal was changed in the order of 10% by mass: 90% by mass, 5% by mass: 95% by mass, and 1% by mass: 99% by mass. The values ​​of the upper limit temperature, optical anisotropy, viscosity, and dielectric anisotropy for the compound were obtained by this extrapolation method.

[0100] The following base liquid crystals were used. The proportions of the component compounds are shown in mass %. TIFF2025009974000034.tif6098

[0101] Measurement method: The characteristics were measured by the following methods. Most of these were methods described in the JEITA standard (JEITA·ED-2521B) established by the Japan Electronics and Information Technology Industries Association (JEITA), or modified methods. No thin film transistors (TFTs) were attached to the TN elements used for the measurements.

[0102] (1) Maximum temperature of nematic phase (NI; °C): A sample was placed on the hot plate of a melting point measuring device equipped with a polarizing microscope and heated at a rate of 1 °C / min. The temperature at which a part of the sample changed from a nematic phase to an isotropic liquid was measured. The maximum temperature of the nematic phase is sometimes abbreviated as the "maximum temperature."

[0103] (2) The minimum temperature of the nematic phase (T C ;°C): A sample having a nematic phase was placed in a glass bottle and stored in a freezer at 0°C, -10°C, -20°C, -30°C, and -40°C for 10 days, after which the liquid crystal phase was observed. For example, when a sample remained in a nematic phase at -20°C and changed to a crystalline or smectic phase at -30°C, T C The lowest temperature of the nematic phase is sometimes abbreviated as "lower limit temperature."

[0104] (3) Viscosity (bulk viscosity; η; measured at 20°C; mPa·s): A Tokyo Keiki E-type rotational viscometer was used for the measurement.

[0105] (4) Viscosity (rotational viscosity; γ1; measured at 25°C; mPa·s): Measurement was performed according to the method described in M. Imai et al., Molecular Crystals and Liquid Crystals, Vol. 259, 37 (1995). A sample was placed in a TN device with a twist angle of 0° and a cell gap of 5μm between the two glass substrates. Voltage was applied to this device in steps of 0.5V increments from 16V to 19.5V. After a 0.2-second period of no voltage application, voltage was applied repeatedly under the conditions of a single square wave (square pulse; 0.2 seconds) and no voltage application (2 seconds). The peak current and peak time of the transient current generated by this voltage application were measured. The value of rotational viscosity was obtained from these measurements and the formula (10) described on page 40 of the paper by M. Imai et al. The value of the dielectric anisotropy required in this calculation was determined by the method described below using the element for measuring the rotational viscosity.

[0106] (5) Optical anisotropy (refractive index anisotropy; Δn; measured at 25°C): Measurements were made using light with a wavelength of 589 nm with an Abbe refractometer equipped with a polarizing plate attached to an eyepiece. After rubbing the surface of the main prism in one direction, a sample was dropped onto the main prism. The refractive index n∥ was measured when the direction of polarized light was parallel to the direction of rubbing. The refractive index n⊥ was measured when the direction of polarized light was perpendicular to the direction of rubbing. The optical anisotropy value was calculated from the formula Δn=n∥-n⊥.

[0107] (6) Dielectric anisotropy (Δε; measured at 25°C): A sample was placed in a TN device with a cell gap of 9μm between two glass substrates and a twist angle of 80°. A sine wave (10V, 1kHz) was applied to this device, and the dielectric constant (ε∥) in the long axis direction of the liquid crystal molecules was measured after 2 seconds. A sine wave (0.5V, 1kHz) was applied to this device, and the dielectric constant (ε⊥) in the short axis direction of the liquid crystal molecules was measured after 2 seconds. The value of the dielectric anisotropy was calculated from the formula Δε=ε∥-ε⊥.

[0108] (7-1) Threshold voltage (Vth(25); measured at 25°C; V): For the measurement, an LCD5200-type luminance meter manufactured by Otsuka Electronics Co., Ltd. was used. The light source was a halogen lamp. A sample was placed in an FFS element with a cell gap of 3.2 (μm) between two glass substrates. The voltage (32 Hz, square wave) applied to this element was increased stepwise by 0.01 V from 0 V to 10 V. At this time, light was irradiated from the vertical direction to measure the amount of light transmitted through the element. A voltage-transmittance curve was created in which the maximum amount of light was the transmittance of 100% and the minimum amount of light was the transmittance of 0%. The threshold voltage was expressed as the voltage at which the transmittance was 90%.

[0109] (7-2) Threshold voltage (Vth(-30); measured at -30°C; V): Same as (7-1) except that it was measured at -30°C.

[0110] (8) Voltage holding ratio (VHR-9; measured at 25°C; %): The TN element used for the measurement had a polyimide alignment film, and the distance (cell gap) between the two glass substrates was 5 μm. After a sample was placed in the element, it was sealed with an adhesive that hardens when exposed to ultraviolet light. A pulse voltage (1 V for 60 microseconds) was applied to the TN element to charge it. The decaying voltage was measured for 1000 milliseconds with a high-speed voltmeter, and the area A between the voltage curve in the unit period and the horizontal axis was calculated. Area B was the area when there was no decay. The voltage holding ratio was expressed as a percentage of area A to area B.

[0111] (9) Voltage holding ratio (VHR-10; measured at 60° C.; %): The voltage holding ratio was measured in the same manner as above, except that the measurement was performed at 60° C. instead of 25° C. The obtained value was expressed as VHR-10.

[0112] (10) Voltage holding ratio (VHR-11; measured at 60°C; %): After irradiation with ultraviolet light, the voltage holding ratio was measured to evaluate the stability against ultraviolet light. The TN element used in the measurement had a polyimide alignment film and a cell gap of 5 μm. A sample was injected into this element, and 5 mW / cm 2The element was irradiated with ultraviolet light of 1000 nm for 167 minutes. The light source was a black light F40T10 / BL (peak wavelength 369 nm) manufactured by iGraphics Co., Ltd., and the distance between the element and the light source was 5 mm. In measuring VHR-11, the voltage decay was measured for 1000 milliseconds. A composition having a large VHR-11 has high stability against ultraviolet light.

[0113] (11) Voltage holding ratio (VHR-12; measured at 60°C; %): After the TN element into which the sample was injected was heated in a thermostatic chamber at 120°C for 20 hours, the voltage holding ratio was measured to evaluate the thermal stability. In the measurement of VHR-12, the voltage decaying over 1000 milliseconds was measured. A composition having a large VHR-12 has a high thermal stability.

[0114] (12) Voltage holding ratio (VHR-13; measured at 60°C; %): The TN element into which the sample was injected was heated in a thermostatic chamber at 100°C for 3 weeks, after which the voltage holding ratio was measured to evaluate the thermal stability. In the measurement of VHR-13, the voltage decayed over 1000 milliseconds was measured. A composition having a large VHR-13 has a high thermal stability.

[0115] (13) Voltage holding ratio (VHR-14; measured at 60°C; %): After the TN element into which the sample was injected was left standing on a backlight for 2 weeks, the voltage holding ratio was measured to evaluate the stability against the backlight. In the measurement of VHR-14, the voltage decayed for 1000 milliseconds was measured. A composition having a large VHR-14 has a high stability against the backlight.

[0116] (14-1) Response time (τ(25); measured at 25°C; ms): An LCD5200 luminance meter manufactured by Otsuka Electronics Co., Ltd. was used for the measurement. The light source was a halogen lamp. The low-pass filter was set to 5 kHz. A sample was placed in an FFS element with a cell gap of 3.2 μm between two glass substrates. A square wave (60 Hz, 5 V, 0.5 seconds) was applied to this element. At this time, light was irradiated from the vertical direction to measure the amount of light transmitted through the element. The maximum amount of light was considered to be 100% transmittance, and the minimum amount of light was considered to be 0% transmittance. The rise time (τr: rise time; milliseconds) is the time required for the transmittance to change from 90% to 10%. The fall time (τf: fall time; milliseconds) is the time required for the transmittance to change from 10% to 90%. The response time was expressed as the sum of the rise time and fall time thus obtained.

[0117] (14-2) Response time (τ(-30); measured at -30°C; ms): Measured at -30°C. Same as (14-1) except that the square wave application conditions were changed (60Hz, 5V, 15 seconds).

[0118] (15) Elastic constant (K; measured at 25°C; pN): A Yokogawa-Hewlett-Packard HP4284A LCR meter was used for the measurement. A sample was placed in a horizontally aligned device with a cell gap of 20 μm between two glass substrates. A charge of 0 to 20 volts was applied to this device, and the capacitance and applied voltage were measured. The measured capacitance (C) and applied voltage (V) were fitted using equations (2.98) and (2.101) on page 75 of the Liquid Crystal Device Handbook (Nikkan Kogyo Shimbun), and the values ​​of K11 and K33 were obtained from equation (2.99). Next, K22 was calculated using the previously obtained values ​​of K11 and K33 in equation (3.18) on page 171 of the same publication. The elastic constant was expressed as the average value of K11, K22, and K33 thus obtained.

[0119] (16) Specific resistance (ρ; measured at 25°C; Ωcm): 1.0 mL of sample was poured into a container equipped with electrodes. A DC voltage (10 V) was applied to the container, and the DC current was measured after 10 seconds. The specific resistance was calculated from the following formula: (Specific resistance) = {(Voltage) x (Capacity of container)} / {(DC current) x (Dielectric constant of vacuum)}.

[0120] (17) Helical pitch (P; measured at room temperature; μm): The helical pitch was measured by the wedge method (see page 196 of "Liquid Crystal Handbook" (published by Maruzen in 2000)). The sample was poured into a wedge-shaped cell and allowed to stand at room temperature for 2 hours, after which the spacing between the disclination lines (d2-d1) was observed under a polarizing microscope (Nikon Corporation, product name MM40 / 60 series). The helical pitch (P) was calculated from the following formula, where the angle of the wedge cell is expressed as θ: P=2×(d2-d1)×tanθ.

[0121] (18) Dielectric constant in the minor axis direction (ε⊥; measured at 25°C): A sample was placed in a TN device with a cell gap of 9 μm between two glass substrates and a twist angle of 80 degrees. A sine wave (0.5 V, 1 kHz) was applied to the device, and the dielectric constant (ε⊥) in the minor axis direction of the liquid crystal molecules was measured after 2 seconds.

[0122] (19) Frequency dependence of dielectric anisotropy (F10; measured at -20°C): A sample was placed in a TN device with a cell gap of 9 μm between two glass substrates and a twist angle of 80 degrees. A sine wave (0.5 V, 100 Hz, 200 Hz, 500 Hz, 800 Hz, 1 kHz, 2 kHz, 5 kHz, 8 kHz, 10 kHz, 20 kHz, 50 kHz, 80 kHz, 100 kHz) was applied to the device, and the dielectric constant (ε⊥) in the minor axis direction of the liquid crystal molecules was measured after 2 seconds. F10 was defined as the frequency at which the dielectric anisotropy decreased by 10% compared to the dielectric anisotropy at 100 Hz. A larger F10 indicates a smaller frequency dependence.

[0123] Compound (1-2-1) was synthesized via the following route. TIFF2025009974000035.tif62147

[0124] Step 1: Synthesis of compound (b) Compound (a) (150g, 0.91mol) was suspended in thionyl chloride (100mL), DMF (5mL) was added, and the mixture was heated under reflux for 3 hours. After cooling, thionyl chloride was removed under reduced pressure to obtain compound (b) (164g, 0.90mol, yield 98.0%).

[0125] Step 2: Synthesis of compound (d) Compound (c) (100 g, 0.61 mol) was dissolved in THF (100 mL), hydrazine monohydrate (100 mL) was added, and the mixture was heated under reflux for 7 hours. After cooling, the mixture was poured into water (500 mL) and the precipitated solid was filtered off. The obtained solid was recrystallized from ethanol (150 mL) to obtain compound (d) (52.4 g, 0.35 mol, yield 57.3%).

[0126] Step 3: Synthesis of compound (e) Compound (d) (120.0 g, 0.80 mol) and compound (b) (131.4 g, 0.72 mol) were suspended in THF (320 mL), pyridine (120 mL) was added, and the mixture was heated under reflux for 5 hours. After cooling, the mixture was poured into water (4 L) and the precipitated solid was filtered off. The obtained solid was recrystallized from ethanol (5 L) to obtain compound (e) (159 g, 0.54 mol, yield 74.6%).

[0127] Step 4: Synthesis of compound (1-2-1) Compound (e) (74.0 g, 0.25 mol) and Lawesson's reagent (100 g, 0.25 mol) were suspended in THF (500 mL) and heated under reflux for 8 hours. After cooling, the mixture was poured into water (500 mL), toluene (500 mL) was added to separate the organic layer, and magnesium sulfate and sodium sulfate were added as drying agents. Furthermore, the solid matter was filtered off, and the filtrate was concentrated under reduced pressure. The obtained solid was purified by column chromatography (toluene) and recrystallized from ethanol (80 mL) to obtain compound (1-2-1) (26.5 g, 0.09 mol, yield 36.0%).

[0128] 1 H-NMR (CDCl3) δ7.90(t,J=8.5Hz,4H),7.29(dd,J=8.5Hz,2.0Hz,4H),2.65(t,J=7.5Hz,2H),2.42(s,3H),1.68(sex,2H),0.97(t,J=7.2Hz,3H).

[0129] Upper temperature limit (NI) = 162.6℃; dielectric anisotropy (Δε) = -5.67; optical anisotropy (Δn) = 0.320; viscosity (η) = 45.1 mPa s.

[0130] Examples of the compositions are shown below. The component compounds are represented by symbols based on the definitions in Table 3 below. In Table 3, the configuration of 1,4-cyclohexylene is trans. The number in parentheses after the symbolized compound indicates the chemical formula to which the compound belongs. The symbol (-) means other liquid crystal compounds. The proportion (percentage) of the liquid crystal compound is a mass percentage (mass %) based on the mass of the liquid crystal composition not including any additives. Finally, the characteristic values ​​of the compositions are summarized.

[0131] TIFF2025009974000036.tif252159

[0132] A composition was prepared that did not contain compound (1). [Comparative Example 1] 3-HHXB(F,F)-F (2-5) 3% 3-GB(F,F)XB(F,F)-F (2-15) 7% 3-GBB(F)B(F,F)-F (2-23) 2% 4-GBB(F)B(F,F)-F (2-23) 2% 3-BB(F,F)XB(F)B(F,F)-F (2-31) 4% 3-HH-V (4-1) 35% V-HH-V1 (4-1) 8% V2-HHB-1 (4-7) 11% 1-BB(F)B-2V (4-10) 3% 2-BB(F)B-2V (4-10) 4% V-HHBB-2 (4-12) 5% V-HHB(2F,3F)-O2 (5-8) 5% 2-HBB(2F,3F)-O2 (5-14) 1% 3-HBB(2F,3F)-O2 (5-14) 5% V-HBB(2F,3F)-O2 (5-14) 5% NI=100.2℃;Tc<-10℃;Δn=0.111;Δε=2.9;ε⊥ / Δε=1.3;γ1=74.7mPa·s.

[0133] Based on the composition of Comparative Example 1, a composition containing compound (1) and having an equivalent NI was prepared. [Example 1] 1-BTdaB-3 (1-2) 7% 3-HHXB(F,F)-F (2-5) 3% 3-GB(F,F)XB(F,F)-F (2-15) 7% 3-GBB(F)B(F,F)-F (2-23) 2% 4-GBB(F)B(F,F)-F (2-23) 2% 3-BB(F,F)XB(F)B(F,F)-F (2-31) 4% 3-HH-V (4-1) 35% V-HH-V1 (4-1) 8% 1V2-HH-3 (4-1) 4% V2-HHB-1 (4-7) 11% 1-BB(F)B-2V (4-10) 3% V-HHBB-2 (4-12) 5% V-HHB(2F,3F)-O2 (5-8) 5% V-HBB(2F,3F)-O2 (5-14) 4% NI=101.4℃;Tc<-40℃;Δn=0.111;Δε=2.9;ε⊥ / Δε=1.3;γ1=67.9mPa·s.

[0134] [Example 2] 1-BTdaB-3 (1-2) 6% 3-HHXB(F,F)-F (2-5) 3% 3-GB(F,F)XB(F,F)-F (2-15) 7% 3-GBB(F)B(F,F)-F (2-23) 2% 4-GBB(F)B(F,F)-F (2-23) 2% 4-BB(F)B(F,F)XB(F,F)-F (2-30) 1.5% 3-BB(F,F)XB(F)B(F,F)-F (2-31) 4% 3-HH-V (4-1) 35% V-HH-V1 (4-1) 8% 3-HB-O2 (4-2) 2% V-HHB-1 (4-7) 1.5% V2-HHB-1 (4-7) 11% 1-BB(F)B-2V (4-10) 2% V-HHBB-2 (4-12) 5% V-HHB(2F,3F)-O2 (5-8) 5% V-HBB(2F,3F)-O2 (5-14) 5% NI = 100.0 °C; Tc < -40 °C; Δn = 0.111; Δε = 3.3; γ1 = 69.0 mPa·s.

[0135] [Example 3] 1-BTdaB-3 (1-2) 5% 3-BB(F,F)XB(F,F)-F (2-19) 6.5% 3-HBBXB(F,F)-F (2-24) 7% 4-BB(F)B(F,F)XB(F,F)-F (2-30) 7% 3-HH-V (4-1) 31% V-HH-V1 (4-1) 8.5% 3-HB-O2 (4-2) 4% 3-HHB-O1 (4-7) 3% V-HHB-1 (4-7) 13% V2-HHB-1 (4-7) 13% 2-BB(F)B-2V (4-10) 2% NI=98.9°C;Tc<-40°C;Δn=0.110;Δε=3.3;γ1=56.8mPa·s.

[0136] [Chapter 4] 1-BTdaB-3 (1-2) 7% 3-BB(F)B(F,F)-CF3(2-17) 3.5% 3-BB(F)B(F,F)XB(F,F)-F (2-30) 4% 4-BB(F)B(F,F)XB(F,F)-F (2-30) 4% 3-BB(F)BC (3-7) 4% 3-HH-V (4-1) 38% V-HH-V1 (4-1) 10% 1V2-HH-1 (4-1) 3% 1V2-HH-3 (4-1) 3.5% V2-BB-1 (4-3) 4.5% 1-BB(F)B-2V (4-10) 10% 2-BB(F)B-2V (4-10) 8.5% NI=81.0°C;Tc<-20°C;Δn=0.140;Δε=3.2;γ1=42.3mPa·s.

[0137] [Chapter 5] 1-BTdB-3(1-2) 8% 2-HB(F)-C (3-1) 3% 3-HB(F)-C (3-1) 5% 3-BB(F)BC (3-7) 10% 3-HH-V (4-1) 35% V-HH-V1 (4-1) 10% V2-BB-1 (4-3) 10% 1-BB(F)B-2V (4-10) 10% 2-BB(F)B-2V (4-10) 9% NI=75.1°C;Tc<-20°C;Δn=0.151;Δε=3.7;γ1=42.1mPa·s.

[0138] [Chapter 6] 1-BTdB-3(1-2) 8% 2-BB-C (3-2) 7.5% 3-BB(F)BC (3-7) 7% 3-HH-V (4-1) 40.5% V-HH-V1 (4-1) 10% V2-BB-1 (4-3) 6% 1-BB(F)B-2V (4-10) 11% 2-BB(F)B-2V (4-10) 10% NI=76.5°C;Tc<-20°C;Δn=0.151;Δε=2.9;γ1=38.4mPa·s.

[0139] [Chapter 7] 1-BTdaB-3 (1-2) 4% 3-HHB-OCF3 (2-2) 2% 3-BB(F)B(F,F)-CF3(2-17) 5% 4-GB(F)B(F,F)XB(F,F)-F (2-28) 3.5% 3-BB(F)B(F,F)XB(F,F)-F (2-30) 3.5% 3-HH-V (4-1) 26.5% V-HH-V1 (4-1) 8% 1V2-HH-3 (4-1) 12% 3-HH-V1 (4-1) 10% 3-HHH-V (4-4) 4% V2-HHB-1 (4-7) 9% 1V2-HHB-1(4-7) 7% 1-BB(F)B-2V (4-10) 5.5% NI=100.8°C;Tc<-20°C;Δn=0.103;Δε=2.4;γ1=56.2mPa·s.

[0140] [Chapter 8] 1-BTdaB-3 (1-2) 4% 3-HHB-OCF3 (2-2) 3.5% 3-BB(F)B(F,F)-CF3 (2-17) 5% 4-GB(F)B(F,F)XB(F,F)-F (2-28) 5% 3-HH-V (4-1) 25.5% V-HH-V1 (4-1) 8% 1V2-HH-3 (4-1) 12% 3-HH-V1 (4-1) 12% 3-HHH-V (4-4) 2% 1V2-HHB-1 (4-7) 3.5% 1-BB(F)B-2V (4-10) 7% 2-BB(F)B-2V (4-10) 8% 3-BB(F)B-2V (4-10) 4.5% NI = 94.3℃; Tc < -20℃; Δn = 0.122; Δε = 2.4; γ1 = 51.4mPa·s.

[0141] [Example 9] 1-BTdaB-3 (1-2) 5% 3-HHB(F,F)-F (2-3) 5% 3-HHBB(F,F)-F (2-20) 5% 3-HBB(F,F)XB(F,F)-F (2-25) 3% 4-GB(F)B(F,F)XB(F,F)-F (2-28) 2% 4-BB(F)B(F,F)XB(F,F)-F (2-30) 6% 3-HH-V (4-1) 30% 3-HH-V1 (4-1) 6% V-HH-V1 (4-1) 8% 1V2-HH-3 (4-1) 5% 3-HHH-V (4-4) 3% V-HHB-1 (4-7) 6% V2-HHB-1 (4-7) 6% 3-HHB(2F,3F)-O2 (5-8) 4% 3-HBB(2F,3F)-O2 (5-14) 4% 3O-Phe(1F,8F)-O2 (5-36) 2% NI=106.6℃;Tc<-30℃;Δn=0.104;Δε=2.5;γ1=68.5mPa·s.

[0142] [Example 10] 1-BTdaB-3 (1-2) 5% 3-HHB(F,F)-F (2-3) 5% 3-HBB(F,F)-F (2-9) 4% 3-HHBB(F,F)-F (2-20) 5% 3-HB(F,F)XB(F,F)-F (2-25) 3% 4-GB(F)B(F,F)XB(F,F)-F (2-28) 2% 4-BB(F)B(F,F)XB(F,F)-F (2-30) 6% 3-HH-V (4-1) 30% 3-HH-V1 (4-1) 6% V-HH-V1 (4-1) 8% 1V2-HH-3 (4-1) 5% 3-HHH-V (4-4) 3% V-HHB-1 (4-7) 6% V2-HHB-1 (4-7) 6% 3O-Phe(1F,8F)-O2 (5-36) 3% 4O-Phe(1F,8F)-O2 (5-36) 3% NI=100.2℃;Tc<-30℃;Δn=0.106;Δε=3.0;γ1=60.3mPa·s.

[0143] The composition of Comparative Example 1 had a rotational viscosity of 74.7 mPa s, and as for the minimum temperature, it was unable to maintain a nematic phase at -20° C. and crystallized. On the other hand, the composition of Example 1 had a rotational viscosity of 67.9 mPa s, and as for the minimum temperature, it did not crystallize at least at -40° C. Therefore, it can be concluded that the liquid crystal composition of the present invention has excellent properties. [Industrial Applicability]

[0144] The liquid crystal composition of the present invention can be used for liquid crystal monitors, liquid crystal televisions, and the like.

Claims

1. A liquid crystal composition having positive dielectric anisotropy, comprising at least one compound selected from the compounds represented by formula (1) as component A: In formula (1), R 1 and R 2 is hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkenyl having 2 to 5 carbon atoms, alkenyloxy having 2 to 5 carbon atoms, or alkyl having 1 to 5 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring A and ring B are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-dioxane, 1,4-phenylene, or 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine; X is sulfur or oxygen; a is 1, 2, or 3; b is 0 or 1; and the sum of a and b is 3 or less.

2. 2. The liquid crystal composition according to claim 1, comprising, as component A, at least one compound selected from the compounds represented by formulas (1-1) to (1-8): In formulas (1-1) to (1-8), R 1 and R 2 is hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkenyl having 2 to 5 carbon atoms, alkenyloxy having 2 to 5 carbon atoms, or alkyl having 1 to 5 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; Y is hydrogen, fluorine, or chlorine.

3. 3. The liquid crystal composition according to claim 1, wherein the proportion of component A is in the range of 3% by mass to 30% by mass.

4. 2. The liquid crystal composition according to claim 1, comprising as component B at least one compound selected from the compounds represented by formulae (2) and (3): In formula (2), R 3 is alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, or alkenyl having 2 to 12 carbon atoms; ring C is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, 2,3-difluoro-1,4-phenylene, 2,6-difluoro-1,4-phenylene, pyrimidine-2,5-diyl, 1,3-dioxane-2,5-diyl, or tetrahydropyran-2,5-diyl; Z 1 is a single bond, ethylene, vinylene, carbonyloxy, or difluoromethyleneoxy; X 1 and X 2 is hydrogen or fluorine; Y 1 is fluorine, chlorine, alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, alkoxy having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, or alkenyloxy having 2 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine; c is 1, 2, 3, or 4; In formula (3), R 4 is alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, or alkenyl having 2 to 12 carbon atoms; Ring D is 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,6-difluoro-1,4-phenylene; Z 2 is a single bond, carbonyloxy, or difluoromethyleneoxy; X 3 and X 4 is hydrogen or fluorine; d is 1, 2, 3, or 4.

5. The liquid crystal composition according to claim 1 or 4, comprising, as component B, at least one compound selected from the compounds represented by formulas (2-1) to (2-36) and formulas (3-1) to (3-8): In formula (2-1) to formula (2-36), R 3 is alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, or alkenyl having 2 to 12 carbons; In formulas (3-1) to (3-8), R 4 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms; X 3 and X 4 is hydrogen or fluorine.

6. The liquid crystal composition according to claim 4 , wherein the proportion of component B is in the range of 5% by mass to 50% by mass.

7. The liquid crystal composition according to claim 1 or 4, comprising as component C at least one compound selected from the compounds represented by formula (4): In formula (4), R 5 and R 6 is an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring E and ring F are 1,4-cyclohexylene, 1,4-phenylene, 2-fluoro-1,4-phenylene, or 2,5-difluoro-1,4-phenylene; Z 3 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy; e is 1, 2, or 3.

8. 2. The liquid crystal composition according to claim 1, comprising, as component C, at least one compound selected from the compounds represented by formulae (4-1) to (4-15): In formulas (4-1) to (4-15), R 5 and R 6 is alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, alkenyl having 2 to 12 carbons, alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine, or alkenyl having 2 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine.

9. The liquid crystal composition according to claim 7 , wherein the proportion of component C is in the range of 10% by mass to 85% by mass.

10. The liquid crystal composition according to claim 7, comprising as component D at least one compound selected from the compounds represented by formula (5): In formula (5), R 7 and R 8 is hydrogen, alkyl having 1 to 12 carbon atoms, alkoxy having 1 to 12 carbon atoms, alkenyl having 2 to 12 carbon atoms, alkenyloxy having 2 to 12 carbon atoms, or alkyl having 1 to 12 carbon atoms in which at least one hydrogen is replaced by fluorine or chlorine; ring G and ring J are 1,4-cyclohexylene, 1,4-cyclohexenylene, tetrahydropyran-2,5-diyl, 1,4-phenylene, 1,4-phenylene in which at least one hydrogen is replaced by fluorine or chlorine, naphthalene-2,6-diyl, naphthalene-2,6-diyl in which at least one hydrogen is replaced by fluorine or chlorine, chroman-2,6-diyl, or at least one hydrogen. ring I is 2,3-difluoro-1,4-phenylene, 2-chloro-3-fluoro-1,4-phenylene, 2,3-difluoro-5-methyl-1,4-phenylene, 1,8-difluorophenanthrene-2,7-diyl, 3,4,5-trifluoronaphthalene-2,6-diyl, 7,8-difluorochroman-2,6-diyl, 3,4,5,6-tetrafluorofluorene-2,7-diyl, 4,6-difluorodibenzofuran-3,7-diyl, 4,6-difluorodibenzothiophene-3,7-diyl, or 1,1,6,7-tetrafluoroindan-2,5-diyl; 4 and Z 5 is a single bond, ethylene, vinylene, methyleneoxy, or carbonyloxy; f is 0, 1, 2, or 3, g is 0 or 1; and the sum of f and g is 3 or less.

11. 8. The liquid crystal composition according to claim 7, comprising, as component D, at least one compound selected from the compounds represented by formulae (5-1) to (5-36): In formula (5-1) to formula (5-36), R 7 and R 8 is hydrogen, alkyl having 1 to 12 carbons, alkoxy having 1 to 12 carbons, alkenyl having 2 to 12 carbons, alkenyloxy having 2 to 12 carbons, or alkyl having 1 to 12 carbons in which at least one hydrogen is replaced by fluorine or chlorine.

12. The liquid crystal composition according to claim 10 , wherein the proportion of component D is in the range of 1% by mass to 20% by mass.

13. A liquid crystal display device comprising the liquid crystal composition according to claim 1 .

14. 14. The liquid crystal display element according to claim 13, wherein an operation mode is a TN mode, an ECB mode, an OCB mode, an IPS mode, an FFS mode, or an FPA mode, and a driving method is an active matrix method.

15. Use of the liquid crystal composition according to any one of claims 1 to 12 in a liquid crystal display device.

Citation Information

Patent Citations

  • Liquid crystal element and liquid crystal device

    JP1998213820A

  • Liquid-crystal medium

    JP2020079385A

  • Liquid crystal medium and liquid crystal display comprising the same

    JP2021165367A

  • Homeotropic sprayed-nematic liquid crystal display device

    WO1997012275A1